The new kinship : constructing donor-conceived families - Cahn, Naomi R. (New York : New York University Press, 2016)
This title details how families are made and how bonds are created between families in the brave new world of reproductive technology. Naomi Cahn, an expert on reproductive technology and the law, shows how these new kinship bonds dramatically exemplify the ongoing cultural change in how we think about family.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Human reproductive technology -- Law and legislation -- Social aspects; Parent and child (Law); Sperm donors -- Legal status, laws, etc; Ovum donors -- Legal status, laws, etc; Human reproductive technology -- Social aspects; Families; Law; United States of America, USA; Ethical issues: scientific, technological & medical developments; Sociology: family & relationships; Laws of specific jurisdictions & specific areas of law; Family law: children